THE ROLE OF ENGLISH PROFICIENCY IN ENHANCING SECRETARIAL STUDENT PERFORMANCE - M Faiz Al Islami Nst; Dela Sarifa Manurung, Rita Hartati (Adisam Publisher, 2025)
This study investigates the impact of English proficiency on the performance of secretarial students, focusing on writing, speaking, listening, and reading skills. Data was collected from 22 students in a Secretaryship program through a descriptive survey. The findings reveal that while a portion of students are confident in their English abilities, many face challenges, particularly in writing professional emails and speaking in class discussions. Listening and reading comprehension also emerged as areas needing improvement. The majority of students recognized that their English proficiency moderately to significantly affects their academic performance in secretarial tasks. The study concludes that enhancing English proficiency through structured practice, feedback, and interactive activities is crucial for preparing students for professional secretarial roles, with recommendations including more writing assignments, role-playing, and speaking exercises to build competence and confidence.